Stress-altering anterior insular cortex activity affects risk decision-making behavior in mice of different sexes - Shi, Tianyao; Feng, Shufang; Zhou, Zhonglin; Li, Fengan; Fu, Yuan; Zhou, Wenxia (Frontiers in Cellular Neuroscience, 2023)
Stress can affect people’s judgment and make them take risky decisions. Abnormal decision-making behavior is a core symptom of psychiatric disorders, such as anxiety, depression, and substance abuse. However, the neuronal mechanisms underlying such impairments are largely unknown. The anterior insular cortex (AIC) is a crucial structure to integrate sensory information with emotional and motivational states. These properties suggest that AIC can influence a subjective prediction in decision-making. In this study, we demonstrated that stressed mice prefer to take more risky choices than control mice using a gambling test. Manipulating the neural activity of AIC or selectively inhibiting the AIC-BLA pathway with chemogenetic intervention resulted in alterations in risk decision-making in mice. Different sexes may have different decision-making strategies in risky situations. Endogenous estrogen levels affect emotional cognition by modulating the stress system function in women. We observed decision-making behavior in mice of different sexes with or without stress experience. The result showed that female mice did not change their choice strategy with increasing risk/reward probability and performed a lower risk preference than male mice after stress. Using the pharmacological method, we bilaterally injected an estrogen receptor (ER) antagonist that resulted in more risky behavior and decreased synaptic plasticity in the AIC of female mice. Our study suggested that the AIC is a crucial region involved in stress-induced alteration of decision-making, and estrogen in the AIC may regulate decision-making behavior by regulating synaptic plasticity.